SISTEM PENDUKUNG KEPUTUSAN KUALITAS LAYANAN PADA PERPUSTAKAAN DAN ARSIP KABUPATEN PIDIE MENGGUNAKAN METODE FUZZY QUALITY FUNCION DEPLOYMENT BERBASIS WEB - Husaini; Rizki Fadhilla (Yayasan Sagita Akademia Maju, 2023)
The library is one of the information centers that is very close and familiar to the community. In addition to the information center, the library is also a source of knowledge, research, and various other services. The library is a vital part and has a big influence on the quality of education. The purpose of this study was to build a decision support system (SPK) using the Fuzzy Quality Function Deployment (QFD) method to determine service quality, the results of which could be used as a reference for libraries and archives in the Pidie district. In the process of knowing the quality of service in the library and archives of the Pidie district using the Fuzzy-QFD method, there are several steps that must be carried out, namely testing the validity of the data in the form of testing the validity of the expectation data, testing the validity of the perception data and calculating the fuzzification of expectations and perceptions to calculating the GAP value for generate rankings. The making of service quality DSS in the library and archives of the Pidie district uses the PHP and MariaDB programming languages ​​as databases for storing data. The results of the research are in the form of an SPK which can be used as a reference in improving the quality of services in the library and archives of the Pidie district